In situ aquatic bioassessment of pesticides applied on rice fields using a microalga and daphnids - Marques, C. R. (2019)
This study assessed the effects of episodic contamination on a drainage canal adjacent to an area of intensive rice production (Coimbra, Portugal). Four monitoring periods were considered [i) before herbicide application (day –14), ii) at the first application day (day 0), iii) 3 or 5 and iv) 6 days after]. Each one consisted in three complementary evaluation lines: a) physico-chemical analyses, b) whole effluent toxicity (WET) assays with Pseudokirchneriella subcapitata, c) in situ bioassays to assess microalgae (P. subcapitata) growth, and the feeding rate and survival of Daphnia longispina and Daphnia magna. Study sites were located upstream, in a protected wetland (L1), and downstream, in the vicinity of rice fields (L2). Along with the application of agrochemicals, there was a general decrease of the water quality, especially in L2, due to nutrient and herbicide inputs. Herbicide peaks (on days 0, 5 and 6) in L2 water samples were recorded concomitantly or immediately after their application. Regarding the in situ bioassessment, the algae growth decrease from day 0 onwards in L1, whilst in L2 its inhibition was generally coherent with the decline of the water quality. Apparently, WET tests indicated that the limitation of nutrients could be affecting algae growth in L1, however, conclusions should be cautious. The feeding depression of daphnids occurred on days 0 and 5 for D. longispina and only on day 0 for D. magna, while significant reductions on survival were restricted to day 0 for both species. The impairments occurring on day 0 were linked to a potential increased toxicity driven by the ingestion of particle-bound herbicides and suspended particles. The feeding rate of daphnids provided an earlier indication of toxic impairments, though it is prompted the use of complementary endpoints and trophic levels in order to understand the cumulative effects due to various herbicide pulses.